2013
DOI: 10.11648/j.ijnfs.20130202.19
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant/Anti-Inflammatory Activities and Chemical Composition of Extracts from the Mushroom Trametes Versicolor

Abstract: Abstract:The mushroom, Trametes versicolor is commonly used as a traditional Chinese medicine and is known to exhibit various biological activities. However, its antioxidant activity has remained unknown. In the present study, various extracts obtained from the Trametes versicolor mushroom were examined for antioxidant and anti-inflammatory activities. Among the extracts obtained with Soxhlet extraction, the extract from acetone exhibited the highest antioxidant activity (50.9%), followed by the extracts from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…18 The DPPH assay was conducted according to a previously reported method. 19 Briefly, a mixture containing a test sample (500 μL/mL) and 300 mM DPPH (500 μL) was incubated at room temperature for 30 min, and then the absorbance at 517 nm was measured using a Hewlett-Packard 8452A diode array spectrophotometer (Hewlett-Packard Co., Palo Alto, CA, USA). Butylated hydroxytoluene Journal of Agricultural and Food Chemistry (BHT; 100 μg/mL) was used as a standard antioxidant to validate the assay.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…18 The DPPH assay was conducted according to a previously reported method. 19 Briefly, a mixture containing a test sample (500 μL/mL) and 300 mM DPPH (500 μL) was incubated at room temperature for 30 min, and then the absorbance at 517 nm was measured using a Hewlett-Packard 8452A diode array spectrophotometer (Hewlett-Packard Co., Palo Alto, CA, USA). Butylated hydroxytoluene Journal of Agricultural and Food Chemistry (BHT; 100 μg/mL) was used as a standard antioxidant to validate the assay.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Kamiyama et al [41] reported that, depending on solvent, extract of T . versicolor fruiting bodies can neutralise up to 50% DPPH•, and Johnsy and Kaviyarasana [40] that methanolic extract of T .…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of using THFA as a fuel results from its relatively high octane number (ON = 83) as well as its physical and chemical similarity to kerosene. Moreover, the products of THFA etherification can be used as diesel fuel additives, reducing emissions of solid particles [3,19,28,[31][32][33][34].Another interesting product of furfural reduction is a pair of tautomers: 5-hydroxy-2-pentanone and 2-methyloxolan-2-ol. These compounds occur naturally in the environment, for example in the Trametes versicolor mushrooms, and probably have antioxidant/anti-inflammatory activities [33].…”
mentioning
confidence: 99%
“…The possibility of using THFA as a fuel results from its relatively high octane number (ON = 83) as well as its physical and chemical similarity to kerosene. Moreover, the products of THFA etherification can be used as diesel fuel additives, reducing emissions of solid particles [3,19,28,[31][32][33][34].…”
mentioning
confidence: 99%
See 1 more Smart Citation